Regulating ridesharing services in S\~ao Paulo - Ciro Biderman (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper explores to what extent a road-use charge levied from transport network companies for their ridesharing services can mitigate negative impacts of ridesharing. This approach is being applied in the city of S\~ao Paulo in Brazil.
Keywords: 330; Autovermietung; Share Economy; Verkehrsstau; City-Maut; Sao Paulo (Stadt)